COMPARATIVE PLANNING FOR PORT CITIES IN SOUTHEAST ASIA AND PERSIAN GULF - Amiri, Sayyed Nouroddin; Norzailawati Mohd Noor; Anafi, Nurin Fadhlina Mohd (Journal of Architecture, Planning and Construction Management, 2023)
Increasing population growth and rapid development of ports are among the challenges of city ports. Today, the relationship between cities and ports has weakened, the historical and cultural connection between ports and cities has been severed, and more decisions are being made on the scale of global management. Ports have lost their former place in the lives of local people. This article compares the ports of the Persian Gulf and Southeast Asia cities. Based on the existing literature, the comparative method is used in economic, environmental, and physical aspects, and the comparative method the similarities and differences between these two geographical regions. The differences and similarities depend on places and countries’ planning and policy methods.